Implementing a revised online screening tool in a routine care online clinic treating anxiety and depression - Mathiasen, Kim; Holmberg Sainte-Marie, Trine Theresa; Skaarnes, Helene; Jensen, Esben Kjems; Vis, Christiaan; Tarp, Kristine (Frontiers in Digital Health, 2023)
Introduction The ItFits implementation toolkit was developed as part of the ImpleMentAll EU Project, to help guide implementation processes. The ItFits toolkit was tested in the online clinic, Internetpsykiatrien, in the Region of Southern Denmark, where it was employed to optimize screening and intake procedures. We hypothesized that a larger proportion of assessed patients would be referred to treatment. Further, we hypothesized the completion rate and effectiveness would increase, as a result of including a more relevant sample. Method Using the ItFits-toolkit, Internetpsykiatrien developed a revised online screening tool. Data on patient flow and symptom questionnaires was extracted from Internetpsykiatrien six months prior to- and six months after implementation of the revised online screening tool. Results A total of 1,830 applicants self-referred for treatment during the study period. A significantly lower proportion of patients were referred to treatment after implementation of the revised screening tool (pre-implementation, n = 1,009; post-implementation, n = 821; odds ratio 0.67, 95% CI: 0.51; 0.87). The number of patients that completed treatment increased significantly (pre-implementation: 136/275 [49.45%], post-implementation, n = 102/162 [62.96%]; odds ratio 1.79, 95% CI 1.20; 2.70). The treatment effect was unchanged (B = 0.01, p = .996). Worth noting, the number of patients that canceled their appointment for the video assessment interview decreased drastically. Conclusion By using the ItFits toolkit for a focused and structured implementation effort, the clinic was able to improve the completion rate, which is an important effect in iCBT. However, contrary to our hypotheses, we did not find an increase in clinical effect, nor a larger ratio being referred to treatment after assessment. The decreased number of referrals for treatment could be a result of increased awareness of inclusion criteria among the clinicians.